Utility of endobronchial ultrasound-guided transbronchial needle aspiration in HIV-infected patients with undiagnosed intrathoracic lymphadenopathy - Prasad, Kuruswamy Thurai (Lung India, 2018)
BACKGROUND: Intrathoracic lymphadenopathy is a common problem in people living with human immunodeficiency virus (PLHIV). There is, however, limited literature on the utility of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in these patients. Herein, we describe our experience with EBUS-TBNA in PLHIV. MATERIALS AND METHODS: This is a retrospective study of all PLHIV who underwent EBUS-TBNA for the evaluation of intrathoracic lymphadenopathy. We also perform a systematic review of the English literature for studies reporting the yield of EBUS-TBNA in PLHIV. RESULTS: During the study, 1733 EBUS procedures were performed. Among them, 22 (1.3%) were performed in PLHIV. The median age of the individuals (18.2% women) was 46 years. The median CD4 count was 144 cells/mm(3). The common lymph node stations involved were station 7, 4R, and 11 L. On endosonographic examination, heterogeneous appearance and coagulation necrosis sign were observed in 14 (63.6%) and 11 (50%) individuals, respectively. EBUS-TBNA was diagnostic in 17 (77.3%) individuals, with tuberculosis being the most common diagnosis (68.2%). There were no major complications related to the procedure. Our systematic review yielded two studies describing the use of EBUS-TBNA in PLHIV. The mean diagnostic yield of EBUS-TBNA was 71% (95% confidence interval: 56–84). CONCLUSIONS: EBUS-TBNA is a safe and useful procedure in the evaluation of intrathoracic lymphadenopathy in PLHIV.